Impulsivity and test meal intake among women with bulimia nervosa. (1st May 2017) - Sysko, Robyn; Ojserkis, Rachel; Schebendach, Janet; Evans, Suzette M.; Hildebrandt, Tom; Walsh, B. Timothy
Abstract: Many patients with bulimia nervosa (BN) also meet criteria for a lifetime alcohol use disorder (AUD). In order to understand possible mechanisms contributing to the co-occurrence and perpetuation of these disorders, this study investigated the importance of impulsivity and test meal intake among patients with BN by comparing women with BN only ( n  = 18), BN and current/past AUDs ( n  = 13), and healthy controls ( n  = 12). All participants completed assessments of eating disorder symptoms, frequency of alcohol use, binge eating, and purging via questionnaires and semi-structured interviews over two sessions. Measures of impulsivity consisted of computerized and self-report measures, and laboratory test meals. Significant differences between individuals with BN with/without comorbid AUDs were not found for test meal intake, impulsivity measures, or self-reported psychological symptoms. As hypothesized, compared to healthy controls, individuals with BN had significantly higher scores on two subscales and the total score of the Barratt Impulsiveness Scale, a trait measure of impulsivity, and consumed significantly more calories in the binge instruction meal. Total Barratt Impulsiveness Scale scores were also significantly related to kcal consumed during the laboratory test meal when individuals were instructed to binge eat (BN groups). Data from this study add to the existing literature implicating impulsivity in the psychopathology of disorders of binge eating, including BN, and also support the use of laboratory meals as a symptom-specific measure of this trait in eating disorder populations.